Blended Learning Station-Rotation Model: Does it Impact on Preservice Teachers' Scientific Literacy? - Gito Hadiprayitno; Kusmiyati Kusmiyati; Ayudya Lestari; Marheny Lukitasari; Akhmad Sukri (Postgraduate, University of Mataram, 2021)
This study aims to test the effectiveness of the blended learning rotation model to improve the scientific literacy skill of prospective teacher students. The design of this study used the Posttest-only design with nonequivalent groups. The research subjects were 76 students majoring in biology education at Universitas Mataram. The research was done to two experimental groups, namely the blended learning station rotation model (BLSRM) and regular learning (RL). The research instrument used a multiple-choice test which refers to the aspects of scientific literacy competence according to PISA. The data analysis technique was carried out descriptively, complete with the Hotelling's T2 test to test the effect of BLSRM on students' scientific literacy skills. The results showed that students' scientific literacy skills were in the very low category (mean BLSRM = 38.50, RL = 34.22) and there was no effect of BLSRM on students' scientific literacy skills (Hotteling Trace = .098 and Sig. = .080). To improve students' scientific literacy skills, BLSRM needs to be combined with other models such as problem-solving model, so it can be an effective strategy in science learning